Memories of “a dead dog”. Notes on the group "Pasado y Presente" - Garrido Fernández, Anxo (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
The current essay is divided in two parts. First, we aim to reconstruct briefly the main milestones in the history of the group Pasado y presente. In the second half, we expose the capital thesis of Juan Carlos Portantiero´s work Los usos de Gramsci as a paradigmatic case of the kind of reading elaborated by members of this Argentine collective.
Keywords: Gramsci; Portantiero; Pasado y Presente; Hegemony; Institution.